Position of Homo sapiens seen from the molecular perspective - Kunicki-Goldfinger, Władysław J. H. (Anthropological Review, 1986)
These studies refer primarily to the proteins and DNA. Works on rRNA and tRNA have a smaller significance in comparison with closely related groups. Comparative studies of proteins were started with the help of immunological methods, mainly precipitation and complement fixation reaction, then Immunoelectrophoresis and electrophoresis in gel were applied, and finally the sequencing of proteins. In the works on DNA the amount of repetitive DNA was determined, renaturalization and hybridization were defined , and then sequencing of DNA, particularly of the one drop DNA. Recently the mitrochondrial DNA started to be studied and quite recently the polymorphism of the length of restrictive segments has been investigated. A supplement of this are the cariological works, studies on the number and structure of chromosomes, their type of striation and the recent studies on the localization of genes. Discussions are carried out on the possibility and limitation of these studies, particularly on the so called melecular clock. Molecular studies refer at present to the living species of Hominidae family and particularly of the subfamily of Homininae with man included. Subsequent discussions refer to the relation of man with apes, their mutual philogenetic relations and the contribution of molecular biology to the achievements of anthropogenesis. Isolated molecular studies on the extinct forms are mentioned. The applicability of molecular methods in the studies on human populations and their value in the investigations on the ethnogenesis and the history of definite populations are discussed. The necessity is stressed that there is a need of a different interpretation of data obtained in the investigation on adaptation features and features with no adaptational values, taking into account not only the investigation of semandides but also the works on the frequency of mutations, on the genetic composition of different populations and the polymorphism of restriction segments. Finally the work discusses briefly the molecular studies of mummies and bones.